Mediated modeling : a system dynamics approach to environmental consensus building - Van den Belt, Marjan (Island Press, 2004)
Annotation A practical guide to participatory modelling for environmental professionals, group-modeling practitioners and students, one that is firmly grounded in the field of systems dynamics and environmental modelling.